2007
DOI: 10.1186/1744-8069-3-28
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Reduces Local Cytokine Expression and Neutrophil Infiltration after Incision

Abstract: Background: Inflammation and nociceptive sensitization are hallmarks of tissue surrounding surgical incisions. Recent studies demonstrate that several cytokines may participate in the enhancement of nociception near these wounds. Since opioids like morphine interact with neutrophils and other immunocytes, it is possible that morphine exerts some of its antinociceptive action after surgical incision by altering the vigor of the inflammatory response. On the other hand, keratinocytes also express opioid receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 47 publications
9
106
0
2
Order By: Relevance
“…Many studies have indicated that opioids are effective for the treatment of postoperative pain and that incisional pain has been classified as opioid sensitive (St A Stewart and Martin, 2003;Whiteside et al, 2004;Clark et al, 2007). In the present study, we found that the effect of tramadol was not completely blocked by 200 μg/kg opioid antagonist naloxone, suggesting that tramadol-induced antinociception may be partially mediated via opioid receptors.…”
Section: Evaluation Of the Opioid Component Of Tramadol On The Presensupporting
confidence: 60%
See 1 more Smart Citation
“…Many studies have indicated that opioids are effective for the treatment of postoperative pain and that incisional pain has been classified as opioid sensitive (St A Stewart and Martin, 2003;Whiteside et al, 2004;Clark et al, 2007). In the present study, we found that the effect of tramadol was not completely blocked by 200 μg/kg opioid antagonist naloxone, suggesting that tramadol-induced antinociception may be partially mediated via opioid receptors.…”
Section: Evaluation Of the Opioid Component Of Tramadol On The Presensupporting
confidence: 60%
“…Opioid analgesics are commonly used for the treatment of both acute (e.g., post-operative) and chronic pain, but some studies argued that they also cause suppression to immune system (Manfredi et al, 1993;Clark et al, 2007). Tramadol hydrochloride is a centrally acting analgesic with opioid and non-opioid like properties (Raffa et al, 1992;Kayser et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies, 50 -52 including ours (unpublished observation), clearly demonstrate the surface expression of mu opioid receptors on keratinocytes. Also, a recent report by Clark et al 48 shows significant inhibition of early KC expression from wound edge keratinocytes following acute morphine treatment. These studies implicate keratinocytes as the potential source of KC synthesis in our model of wound healing and morphine modulation of KC synthesis may be mediated through mu opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in support of wounding as a potent stimulus for KC secretion is provided by several recent reports. 48,49 These studies identify wound edge keratinocytes as an important source of cytokines in the acute phase following wounding and KC as the predominant chemokine present at enhanced levels at wound sites following incision. Although our studies show significant decrease in the early expression of KC following morphine treatment, the cell type responsible for KC expression was not identified.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explain the histological differences, we evaluated the immunological background of the lesions. Recent studies have demonstrated that stimulated keratinocytes can secrete neuropeptides, such as substance P (SP), and pro-inflammatory cytokines like IL-1α, IL-1β, IL-6 and TNF-α 8,9 . In addition, extravasated mucus can induce extensive macrophage reactions 10 .…”
Section: Discussionmentioning
confidence: 99%